Role of bilateral internal iliac artery ligation in controlling refractory post partum hemorrhage - Jamil, Samia; Munir, sara; Amin, Javeria; Nourin, Shazia; ., Alia; e huma, Zill; Saeed Khokhar, Hamza; Ul Moazzam, Sultan; Sohail Afzal, Muhammad (International Journal of Medicine, 2021)
Background: Post Partum Hemorrhage (PPH) is a life threatening emergency that needs to be managed timely. Refractory PPH is treated surgically. Bilateral internal iliac artery ligation is one of the surgical procedures performed to control bleeding.Objective: We analyzed the effectiveness of Bilateral IIAL in controlling bleeding in PPHMethodology: It was a retrograde cross-sectional study conducted at Lady Aitchison hospital, Lahore from data during January 2018 to December 2020. After applying inclusion and exclusion criteria, data of patient including demographics, history, examination, ultrasound, procedure details and post-operative complications were recorded. All the data was analyzed using SPSS version 23.0.Results: All the patients (44) survived and success rate was 100 %. Uterine atony was present in 29 (65.9%) patients as a cause of PPH, placental abnormality, uterine rupture and coagulopathy in 7(15, 9), 4 (9.1%) and 4 (9.1%) patients respectively. 17 patients did not develop any complication. Most common Post-operative complication was wound infection (22.75%) followed by pneumonia (20.5%), paralytic ileus (9.1%) and DIC with renal failure (9.1%).Conclusion: Bilateral IIAL was found to be an effective and preferred life saving procedure, preserving fertility.Â Â Â